ANALISA PEMBERIAN KOMPENSASI PADA PT. TESO INDAH KABUPATEN INDRAGIRI HULU - Firman Hadi; Zulkifli M.Si (VALUTA, 2015)
This study aims to look at how the implementation of Providing Compensation forpermanent and temporary employees at PT. Teso Indah the District of Indragiri Hulu.Assessment indicators, namely salaries, incentives, wages, working facilities, benefitsand retirement security, disaster relief and compensation, employee insurance, otherfacilities. This type of research located in PT. Teso Indah Indragiri Hulu is descriptive,which is to prioritize the list of the questionnaire as a data collector and data collectedby the tool is then used as the main raw material for evaluating the condition ofempirical and objective research purposes at locations where carefully. There are twogroups of the population and sample in this research is the employee fixed and variablenumbering 50 people and 43 people. The sampling technique used in determining theindividual sample is census techniques. Types and data collection techniques usedconsisted of primary data collected by using a list of questionnaires and interviews andsecondary data was collected using observation or direct observation of the place ofstudy sites. Data analysis technique that classification data in the form of a type andmake descriptive of the findings in the study were analyzed quantitatively as well as thequality that comes with the percentage data. Once the data is analyzed then proceed tomake conclusions and suggestions of research results. The conclusions andrecommendations of the research concerning the granting of compensation to PT.TesoIndah Indragiri Hulu categorized not good with advice further enhance thecompensation granted to employees and non-permanent and shall be in accordancewith the compensation they received with their level of quality. Then facilities providedmore attention and more cared for.